A Comparative Study of Saudi and International Journals of Applied Linguistics: The Move-Bundle Connection Approach - Basim Alamri (National Research University Higher School of Economics, 2020)
The present study implemented a genre-based approach to analyze the rhetorical structure of English language research articles (RAs): specifically, the Introduction-Methods-Results-Discussion-Conclusion (I-M-R-D-C) sections. Next, lexical bundles (LBs) associated with patterns of moves were identified by applying a corpus-driven approach. The study analyzed two corpora of 30 RAs purposely selected from 16 peer-reviewed journals of applied linguistics published in Saudi Arabia and internationally during the years of 2011-2016. First, a genre-based approach was used to identify the move structures of RAs through analyzing different RA sections by different models. Next, lexical bundles associated with each identified move in each IMRDC section were analyzed using a corpus-driven approach, based on structural and functional taxonomies. The study findings showed that both corpora share similarities and differences related to rhetorical structures and lexical bundles. These findings have pedagogical implications for novice writers, graduate students, and English for Academic Purposes (EAP) instruction, including raising awareness of rhetorical structures and LBs in academic writing for publication, which could help produce more successful publishable research articles.